Mutation screening of pre-eclampsia candidate genes, LEP (ob) and LEPR (obR) - Hoek, Kim G. P. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Genetics))--University of Stellenbosch, 2006.